Decoding Myth and Ideology: A Semiotic Study of Smartphone Advertisements - Km Tri Sutrisna Agustia; Ni Luh Sutjiati Beratha; I Wayan Pastika; I Nyoman Udayana (International Journal Labs, 2024)
Smartphones are becoming more ingrained in daily life, and the way they are marketed on platforms like YouTube will continue to shape societal attitudes toward technology, progress, and consumerism. This study explores the formation of myths and ideologies in smartphone advertisements from YouTube, utilizing semiotic analysis as its primary framework. The study focuses on two specific smartphone ads from YouTube: the Oppo Reno 12 campaign titled